Rehmannia glutinosa Replant Issues: Root Exudate-Rhizobiome Interactions Clearly Influence Replant Success - Zhang, Bao; Weston, Leslie A.; Li, Mingjie; Zhu, Xiaocheng; Weston, Paul A.; Feng, Fajie; Zhang, Bingyong; Zhang, Liuji; Gu, Li; Zhang, Zhongyi (Frontiers in Microbiology, 2020)
Production of medicinal tubers of Rehmannia glutinosa are severely hindered by replanting problems. However, a mechanistic understanding of the plant-soil factors associated with replant problems is currently limited. Thus, we aimed to identify the R. glutinosa root exudates, evaluate their phytotoxicity and profile the interactions between the plant and its associated rhizobiome. Stereomicroscopy and liquid chromatography coupled to a quadrupole/time of flight mass spectrometer were used to monitor and identify secreted metabolites, respectively. Seed-bioassays were used to evaluate the allelopathy of candidate phytotoxins. Two complimentary experiments were performed to investigate allelochemical fate in rhizosphere soil and impact on associated microbiota. Catalpol and six phenylethanoid glycosides were identified in R. glutinosa root exudates and the rhizosphere soil using metabolic profiling. Quantification and phytotoxic analysis showed catalpol was the most abundant and bioactive known metabolite released from R. glutinosa. Subsequent microbial profiling in soil containing accumulated and ecologically significant levels of catalpol identified several taxa were specifically enriched, suggesting catalpol was involved in the complex plant-soil chemical signaling. The identification of key R. glutinosa root exudates and profiling of rhizobiome are a critical first step in understanding the mechanisms associated with R. glutinosa replanting failure.